DESIGNING A PROMOTION MEDIA OF SMP SANTA MARIA II SIDOARJO - Worabai, Dave Edwards Maurgi; Arumsari, Rizki Yantami; Nurbani, Sri (eProceedings of Art & Design, 2024)
The advancement of science and technology mandates adaptive change to stay current. Knowledge's pivotal role in enhancing societal competitiveness is recognized. Education is a strategic tool, fostering intelligence, skills, and positive attitudes for effective societal integration. Schools, through education, cultivate human potential and form positive identities. Law 20/2003 defines education as a means todevelop human potential. Education's root in "educate" underscores its training role. Education attainment involves school competition, necessitating essential marketing for academic institutions. Schools, as service providers, must enhance student satisfaction through initiatives and marketing strategies. Sales promotion, part of the marketing mix, adds value and incentives for direct or short-term sales, fostering loyalty, and brand awareness. Media promotion introduces products to communities, sustaining institutions' presence and reputation. Effective promotion aids schools in maintaining visibility and enrollment. Promotional efforts should align with marketing principles, though challenges persist in achieving desired outcomes. Enhanced education quality and resource allocation can be attained through improved facilities and infrastructure, enhancing student-centered learning environments. SMP Santa Maria II, Sidoarjo, a leading Catholic school, faces stiff competition and enrollment challenges. Despite efforts, it hasn't secured desired status, necessitating improved promotional strategies. This issue motivates the research titled "DESIGNING A PROMOTION MEDIA OF SANTA MARIA II JUNIOR HIGH SCHOOL, SIDOARJO." Keywords: junior high school, promotion media, SMP Santa Maria II Sidoarjo